Vitreous Substitutes: The Present and the Future. (3rd May 2014) - Donati, Simone; Caprani, Simona Maria; Airaghi, Giulia; Vinciguerra, Riccardo; Bartalena, Luigi; Testa, Francesco; Mariotti, Cesare; Porta, Giovanni; Simonelli, Francesca; Azzolini, Claudio
Abstract : Vitreoretinal surgery has advanced in numerous directions during recent years. The removal of the vitreous body is one of the main characteristics of this surgical procedure. Several molecules have been tested in the past to fill the vitreous cavity and to mimic its functions. We here review the currently available vitreous substitutes, focusing on their molecular properties and functions, together with their adverse effects. Afterwards we describe the characteristics of the ideal vitreous substitute. The challenges facing every ophthalmology researcher are to reach a long-term intraocular permanence of vitreous substitute with total inertness of the molecule injected and the control of inflammatory reactions. We report new polymers with gelification characteristics and smart hydrogels representing the future of vitreoretinal surgery. Finally, we describe the current studies on vitreous regeneration and cell cultures to create new intraocular gels with optimal biocompatibility and rheological properties.